Strategies for pregnant womens’s adherence in prenatal consultations in the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: SARS-COV-2, the etiological agent of COVID-19, has spread rapidly worldwide, making pregnant women vulnerable, among other groups. In view of the complications for pregnancy and the fetus, it is necessary to reflect on prenatal care in times of a COVID-19 pandemic and the importance of professional care. Objective: Search the available literature for strategies for the adherence of pregnant women to prenatal consultations during the COVID-19 pandemic. Methodology: Integrative, descriptive-explorative review, evidenced in integrative, systematized and qualified analysis, developed through research on online platforms: BIREME and PUBMED, using the descriptors: Pregnant women; Prenatal care and COVID-19. 234 articles were identified in the search platforms, and after applying the inclusion and exclusion criteria and analyzing the studies, 16 articles were selected to compose the present work. Results and discussion: The studies recommend the use of telemedicine/telenursing in prenatal consultations, in addition to intervals between consultations and exams to avoid exposing pregnant women to the high risk of contagion. Preventive measures should also be adopted, such as the use of personal protective equipment (PPE) such as a mask, apron and gel alcohol, in addition to the adoption of social distance. Final considerations: it was noted that telemedicine, the reorganization of face-to-face consultations, the attire and qualification of professionals are the strategies used, and that lead to positive results, thus favoring the reduction of the spread of the virus and the increase of the health promotion of the women. pregnant women.